Prevalence and Risk Factors of Polycystic Ovary Syndrome (PCOS) among Medical Students of a Private Medical College in Lahore (Journal of Fatima Jinnah Medical University, 2024)
Background: Polycystic ovary syndrome (PCOS) is thought to be among the most frequent causes of infertility within the female population, affecting 4-18% of the women in reproductive age worldwide. The study environment, the challenges that medical students face are different from that of other professional degrees. The primary objective of this study was to determine the prevalence of polycystic ovary syndrome (PCOS) symptoms and secondary objective were to identify risk factors among medical students.Subjects and methods: A cross sectional study was conducted on 289 medical students of CMH Lahore Medical College and Institute of Dentistry. The inclusion criteria were female students willing to participate and the exclusion criteria were female students unwilling to participate. Questionnaire based responses were obtained from 289 female students. Data was entered in SPSS version 27.0 and analyzed.Results: It was observed that 8% females were known to have PCOS. There was a significant relation between PCOS and weight gain (p= 0.024), family history of PCOS (p= 0.039) and family history of hypertension (p= 0.018). A significant relation was noted between PCOS and irregular periods (p= 0.009), acne (p= 0.040) and excessive hair growth on the body (p=0.003).Conclusion: PCOS was found to be prevalent. Weight, family history of PCOS and family history of hypertension were found to be the main risk factors whereas irregular periods, acne and hirsutism were the main clinical features observed.
Keywords: Polycystic Ovary Syndrome; Medical students; Risk factors; Prevalence; Awareness